Analysis of Factors Affecting Original Local Government Revenue (PAD) in Central Bangka Regency - Altin, Darus; Yusnita, Maya; Wulandari, Ayu (FEB - Universitas Lampung, 2021)
The purpose of this study is to determine the potential of Original Local Government Revenue (PAD), the factors that influence PAD and the problems and obstacles faced by the Central Bangka Regency Government in increasing PAD. The analysis technique uses descriptive analysis and multiple regression. The findings in this study show population, GRDP and inflation positive and significant effect on the PAD of Central Bangka Regency.The income of an area can be obtained from population activities in the economy which have an impact on increasing PAD. The biggest contribution to GRDP Central Bangka Regency in 2021 from the Agriculture, Forestry and Fisheries Sector; Wholesale and Retail Trade Sector; Car and Motorcycle Repair; and the Mining and Excavation Sector which is expected in the future to become a leading sector in increasing PAD.